Glue solution for halogen-free antimony-free flame-retardant laminated board, prepreg, laminated board, manufacturing method and resin composition
By adopting a variety of resin combinations and inorganic fillers, the thermal conductivity, flame retardancy and electrical insulation performance of the FR-4 laminate is improved, and the problems of low thermal conductivity, low CTI and flame retardant systems in the prior art are solved, achieving efficient and environmentally friendly performance improvement.
Patent Information
- Application Number
- CN202510251201.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-04-29
AI Technical Summary
The existing FR-4 laminates have low thermal conductivity, low CTI, and flame retardant systems that rely on halogen or antimony, which are difficult to meet the needs of efficient heat dissipation, environmental protection and high electrical insulation performance, especially in high temperature and harsh environments.
A variety of resin combinations are adopted, including bisphenol A type epoxy resin, DOPO type modified phosphorus-containing epoxy resin, bisphenol A phenolic epoxy resin, etc., combined with inorganic fillers such as graphene oxide and aluminum hydroxide, the thermal conductivity, flame retardancy and electrical insulation properties of the laminate are improved by the combination of modified resin and filler.
The advantages of the laminate are achieved with high thermal conductivity, CTI≥600 V, TG≥155℃, halogen and antimony-free, meet the needs of efficient heat dissipation, environmental protection and high electrical insulation performance, and reduce production costs.
Smart Images

Figure CN119899491A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an adhesive solution for a halogen-free and antimony-free flame-retardant laminate, a prepreg, a laminate, a manufacturing method and a resin composition. Background Art
[0002] In the field of electronics and electrical, as products develop rapidly towards miniaturization, high performance and high reliability, the requirements for basic materials such as laminates are becoming increasingly stringent.
[0003] Although traditional FR-4 laminates are widely used, they have many limitations. On the one hand, their thermal conductivity is low. When electronic components are running at high power, heat is difficult to dissipate quickly, which can easily lead to local overheating, thus affecting the stability and life of electronic equipment. For example, in areas where heat dissipation is urgent, such as smartphones and computer CPU peripherals, ordinary FR-4 cannot meet the requirements of efficient heat dissipation, which may cause problems such as frequency reduction and freezing of the device.
[0004] On the other hand, the flame retardant system of traditional FR-4 often relies on halogen or antimony compounds. Halogen-containing flame retardants release a large amount of toxic and harmful gases, such as hydrogen bromide, when burned, which not only poses a serious threat to human health, but also causes serious secondary pollution in fire scenes. Although antimony-containing compounds can synergistically flame retardant, the antimony element itself has certain biological toxicity, which is not conducive to long-term use from the perspective of environmental protection and sustainable development.
[0005] At the same time, as the working environment of electronic products becomes more and more complex, the requirements for the electrical insulation performance of materials are also increasing. In contrast, the comparative tracking index (CTI) value of ordinary FR-4 is often low, which is difficult to meet the needs of some electronic equipment working under harsh conditions such as humidity and high voltage, and is prone to safety hazards such as leakage and short circuit.
[0006] In addition, the heat resistance requirements of electronic products have also prompted laminates to develop towards high glass transition temperatures (TG). Laminates with medium-high TG ("medium-high TG" generally refers to TG ≥ 140°C) can maintain good mechanical properties and dimensional stability in high temperature environments, avoiding deformation and warping due to temperature increases, which in turn affects the welding and assembly accuracy of electronic components.
[0007] However, most existing laminates face challenges in achieving TG ≥ 155°C. Furthermore, there are huge challenges in achieving the synergistic improvement of high thermal conductivity, halogen-free and antimony-free flame retardancy, high CTI and TG ≥ 155°C. There is an urgent need to develop a low-cost, multi-performance laminate that meets TG ≥ 155°C to fill this technological gap. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the defect of low TG of FR-4 laminate in the prior art, and provide a halogen-free and antimony-free flame-retardant laminate adhesive, prepreg, laminate, manufacturing method, and resin composition. The adhesive in the present invention can achieve TG ≥ 155°C for copper clad laminates, and further, can overcome the defects of low thermal conductivity, low CTI, and flame retardant system of FR-4 laminate in the prior art that often rely on halogen or antimony compounds.
[0009] The inventors of the present invention creatively adopt a combination of multiple resins and select resins with lower costs in the industry, such as bisphenol A epoxy resin (such as NPEL128 produced by Kunshan Nan Ya), which reduces costs while ensuring the performance of the board.
[0010] The present invention provides a resin composition, which comprises the following components in parts by mass:
[0011] 360-440 parts of bisphenol A epoxy resin, wherein the bisphenol A epoxy resin has an epoxy equivalent of 185-190 g / eq and a viscosity of 12000-15000 mPa·s at 25° C.;
[0012] 1260-1540 parts of a DOPO type modified phosphorus-containing epoxy resin, wherein the DOPO type modified phosphorus-containing epoxy resin has an epoxy equivalent of 295-335 g / eq;
[0013] 180-220 parts of bisphenol A novolac epoxy resin, wherein the epoxy equivalent of the bisphenol A novolac epoxy resin is 190-220 g / eq;
[0014] 90-110 parts of a novolac epoxy resin, wherein the novolac epoxy resin has an epoxy equivalent of 176-181 g / eq;
[0015] 270-330 parts of bisphenol A type phosphorus-containing phenolic resin, wherein the viscosity of the bisphenol A type phosphorus-containing phenolic resin at 25° C. is 500-2500 mPa.s;
[0016] 90-110 parts of a tetrafunctional novolac epoxy resin, wherein the epoxy equivalent of the tetrafunctional novolac epoxy resin is 200-220 g / eq.
[0017] In some embodiments of the present invention, the bisphenol A epoxy resin may be NPEL128E produced by Kunshan Nan Ya.
[0018] In some embodiments of the present invention, the solid content of the bisphenol A epoxy resin is 100%.
[0019] In some embodiments of the present invention, the mass fraction of the bisphenol A epoxy resin is 400 parts.
[0020] In some embodiments of the present invention, the DOPO-type modified phosphorus-containing epoxy resin may be DFE202 produced by Sichuan Dongcai.
[0021] In some embodiments of the present invention, the solid content of the DOPO-type modified phosphorus-containing epoxy resin is 70-80%, for example 75%.
[0022] In some embodiments of the present invention, the phosphorus content of the DOPO-type modified phosphorus-containing epoxy resin is 3.1-3.2%.
[0023] In some embodiments of the present invention, the mass fraction of the DOPO type modified phosphorus-containing epoxy resin is 1400 parts.
[0024] In some embodiments of the present invention, the bisphenol A novolac epoxy resin is SQAN-201EK80 produced by Shengquan.
[0025] In some embodiments of the present invention, the solid content of the bisphenol A novolac epoxy resin is 75-85%, for example 80%.
[0026] In some embodiments of the present invention, the mass fraction of the bisphenol A novolac epoxy resin is 200 parts.
[0027] In some embodiments of the present invention, the phenolic epoxy resin may be DEN438 EK85J phenolic epoxy resin produced by Dow.
[0028] In some embodiments of the present invention, the solid content of the phenolic epoxy resin is 80-90%, for example 85%.
[0029] In some embodiments of the present invention, the viscosity of the novolac epoxy resin at 25° C. is 600-1600 mPa.s.
[0030] In some embodiments of the present invention, the mass fraction of the phenolic epoxy resin is 100 parts.
[0031] In some embodiments of the present invention, the bisphenol A type phosphorus-containing phenolic resin is XZ92741 produced by Dow.
[0032] In some embodiments of the present invention, the solid content of the bisphenol A type phosphorus-containing phenolic resin is 56-58%.
[0033] In some embodiments of the present invention, the phosphorus content of the bisphenol A type phosphorus-containing phenolic resin is 9-10%.
[0034] In some embodiments of the present invention, the mass fraction of the bisphenol A type phosphorus-containing phenolic resin is 300 parts.
[0035] In some embodiments of the present invention, the tetrafunctional phenolic epoxy resin is NPPN431A70 produced by Kunshan Nan Ya.
[0036] In some embodiments of the present invention, the solid content of the tetrafunctional phenolic epoxy resin is 65-75%, for example 70%.
[0037] In some embodiments of the present invention, the softening point of the tetrafunctional novolac epoxy resin is 82-92°C.
[0038] In some embodiments of the present invention, the mass fraction of the tetrafunctional phenolic epoxy resin is 100 parts.
[0039] In some embodiments of the present invention, the mass ratio of the bisphenol A epoxy resin, the DOPO modified phosphorus-containing epoxy resin, the bisphenol A novolac epoxy resin, the novolac epoxy resin, the bisphenol A phosphorus-containing novolac resin, and the tetrafunctional novolac epoxy resin is 4:14:2:1:3:1.
[0040] The present invention also provides a raw material composition of an adhesive for a halogen-free and antimony-free flame-retardant laminate, which comprises the following components in parts by mass:
[0041] 360-440 parts of bisphenol A epoxy resin, wherein the bisphenol A epoxy resin has an epoxy equivalent of 185-190 g / eq and a viscosity of 12000-15000 mPa·s at 25° C.;
[0042] 1260-1540 parts of a DOPO type modified phosphorus-containing epoxy resin, wherein the DOPO type modified phosphorus-containing epoxy resin has an epoxy equivalent of 295-335 g / eq;
[0043] 180-220 parts of bisphenol A novolac epoxy resin, wherein the epoxy equivalent of the bisphenol A novolac epoxy resin is 190-220 g / eq;
[0044] 90-110 parts of a novolac epoxy resin, wherein the novolac epoxy resin has an epoxy equivalent of 176-181 g / eq;
[0045] 270-330 parts of bisphenol A type phosphorus-containing phenolic resin, wherein the viscosity of the bisphenol A type phosphorus-containing phenolic resin at 25° C. is 500-2500 mPa.s;
[0046] 90-110 parts of a tetrafunctional novolac epoxy resin, wherein the epoxy equivalent of the tetrafunctional novolac epoxy resin is 200-220 g / eq;
[0047] Solvents;
[0048] 72-88 parts of curing agent;
[0049] 0.5-1.5 parts of curing accelerator;
[0050] 18-22 parts of silane coupling agent;
[0051] Optionally, the raw material further comprises an inorganic filler.
[0052] In the present invention, the resin raw material can be as described above.
[0053] In the present invention, the solvent may be any conventional solvent in the art that can dissolve the raw material composition.
[0054] In some embodiments of the present invention, the solvent includes a mixed solvent 1 and a mixed solvent 2, wherein the mixed solvent 1 is a solvent that can dissolve a curing agent, a curing accelerator and some inorganic fillers, and the mixed solvent 2 is a solvent that can dissolve a coupling agent and a resin.
[0055] In some embodiments of the present invention, the mixed solvent 1 is a mixed system of DMF and other solvents to dissolve the curing agent (such as DICY) and the curing accelerator (such as imidazole), and the mixing ratio is adjusted to reduce the amount of DMF used.
[0056] In some embodiments of the present invention, the mixed solvent 1 includes DMF (N,N-dimethylformamide), ethanol, dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL), and the mass ratio of DMF, ethanol, dimethyl sulfoxide, and γ-butyrolactone can be 5:3:1:1.
[0057] In the present invention, a mixed solvent 1 (for example, a mass ratio of 5:3:1:1) comprising DMF, ethanol, dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL) can ensure solubility while utilizing the volatility of ethanol to make the solvent system easier to remove during the drying process, thereby reducing the DMF content in the plate.
[0058] In some embodiments of the present invention, the mixed solvent 2 is a mixture of propylene glycol methyl ether (PM) and other solvents to dissolve the resin, and the mixing ratio is adjusted to reduce the amount of DMF used.
[0059] In some embodiments of the present invention, the mixed solvent 2 comprises PM, ethyl acetate, and isopropanol, and the mass ratio of PM, ethyl acetate, and isopropanol may be 5:3:2.
[0060] In the present invention, the hydroxyl and methoxy groups of PM in the mixed solvent 2 can form hydrogen bonds and other interactions with the polar part of the halogen-free resin, the ester bond structure of ethyl acetate can generate affinity with similar ester bond structures in the resin, and isopropanol contains hydroxyl groups. After mixing, the dissolution effect on the hydroxyl-sensitive part in the halogen-free resin can be enhanced.
[0061] In some embodiments of the present invention, the mass fraction of the mixed solvent 1 is 450-550 parts, for example, 500 parts.
[0062] In some embodiments of the present invention, the mass fraction of the mixed solvent 2 is 135-165 parts, for example, 150 parts.
[0063] In some embodiments of the present invention, the mass fraction of the curing agent is 80 parts.
[0064] In some embodiments of the present invention, the curing agent is DDS (4,4'-diaminodiphenyl sulfone) and / or DICY (dicyandiamide).
[0065] In some embodiments of the present invention, the mass fraction of DICY (dicyandiamide) is 45-55 parts, for example, 50 parts.
[0066] In some embodiments of the present invention, the mass fraction of the DDS (4,4'-diaminodiphenyl sulfone) is 27-33 parts, for example, 30 parts.
[0067] In some embodiments of the present invention, the mass ratio of the DICY to the DDS is 5:3.
[0068] In some embodiments of the present invention, the curing accelerator is diphenylimidazole.
[0069] In some embodiments of the present invention, the mass fraction of the curing accelerator is 0.9-1.1 parts, for example, 1.0 parts.
[0070] In some embodiments of the present invention, the silane coupling agent is KH-570, and its chemical name is γ-methacryloxypropyltrimethoxysilane.
[0071] In some embodiments of the present invention, the unsaturated double bonds in the molecular structure of the silane coupling agent can participate in free radical polymerization reactions and can be better combined with some resin systems containing unsaturated bonds. In the production of halogen-free copper clad laminates, the wettability and coating of the resin on inorganic fillers can be improved, the dispersibility of the fillers in the resin can be enhanced, and the mechanical properties and electrical insulation properties of the copper clad laminates can be improved, which is particularly suitable for halogen-free copper clad laminates with high requirements for water resistance and weather resistance.
[0072] In some embodiments of the present invention, the mass fraction of the silane coupling agent is 20 parts.
[0073] In some embodiments of the present invention, the inorganic filler includes graphene oxide.
[0074] Graphene oxide has certain flame retardant properties and can partially replace traditional flame retardants in halogen-free copper clad laminates, reducing the amount of flame retardants used, while improving the flame retardant and environmental performance of copper clad laminates; its flame retardant mechanism is mainly to form a carbon layer during the combustion process to prevent the transfer of heat and oxygen, thereby achieving the purpose of flame retardancy.
[0075] In some embodiments of the present invention, the mass fraction of the graphene oxide is 45-55 parts, for example, 50 parts.
[0076] In some embodiments of the present invention, the graphene oxide is a single layer.
[0077] In some embodiments of the present invention, the thickness of the graphene oxide is 0.8 nm-1.2 nm.
[0078] In some embodiments of the present invention, the specific surface area of the graphene oxide is 500m² / g-1000m² / g.
[0079] In some embodiments of the present invention, the carbon-oxygen ratio of the graphene oxide is between 2-4.
[0080] In some embodiments of the present invention, the inorganic filler further includes spherical aluminum oxide and / or aluminum hydroxide.
[0081] The aluminum hydroxide in the present invention can be used as a flame retardant to reduce the decomposition of the material surface and the formation of carbon particles, thereby significantly improving the flame retardancy of the material and reducing the thermal expansion coefficient and water absorption rate of the plate.
[0082] In the present invention, the spherical alumina can effectively improve the thermal conductivity of the copper-clad laminate, accelerate heat dissipation, and reduce its dielectric constant and thermal expansion coefficient.
[0083] In some embodiments of the present invention, the sum of the mass fractions of the spherical aluminum oxide and / or aluminum hydroxide is 1080-1320 parts, for example, 1200 parts.
[0084] In some embodiments of the present invention, the mass fraction of the aluminum hydroxide is 900-1100 parts, for example, 1000 parts.
[0085] In some embodiments of the present invention, the grade of the aluminum hydroxide is MARTINAL® OL-104LEO.
[0086] In some embodiments of the present invention, the purity of the aluminum hydroxide is ≥99.6%, and the whiteness is ≥93.
[0087] In some embodiments of the present invention, the particle size range of the aluminum hydroxide is: D50, 1.9±0.2 μm; D90, 3.2±1.0 μm.
[0088] In some embodiments of the present invention, the oil absorption rate of the aluminum hydroxide is 27-32 ml / 100g.
[0089] In some embodiments of the present invention, the conductivity of the aluminum hydroxide (10%, in water) is: 20 μS / cm.
[0090] In some embodiments of the present invention, the mass fraction of the spherical aluminum oxide is 180-220 parts, for example, 200 parts.
[0091] In some embodiments of the present invention, the grade of the spherical alumina is SLA-5.
[0092] In some embodiments of the present invention, the D50 particle size of the spherical alumina is 5±1 μm.
[0093] In some embodiments of the present invention, the D90 particle size of the spherical alumina is 15±3 μm.
[0094] In some embodiments of the present invention, the mass ratio of the spherical aluminum oxide to the aluminum hydroxide is 1:5.
[0095] In some embodiments of the present invention, the mass fraction of the inorganic filler is 1125-1375 parts, for example, 1250 parts.
[0096] In some embodiments of the present invention, the composition of the raw material composition is shown in the following table:
[0097] ;
[0099] in:
[0100] The mixed solvent 1 refers to a mixed solvent of N,N-dimethylformamide DMF, ethanol, dimethyl sulfoxide DMSO, and γ-butyrolactone GBL in a mass ratio of 5:3:1:1;
[0101] The mixed solvent 2 refers to a mixed solvent in which propylene glycol methyl ether PM, ethyl acetate EA and isopropanol have a mass ratio of 5:3:2.
[0102] The present invention also provides a method for preparing a halogen-free and antimony-free flame-retardant adhesive for laminated boards, which comprises the following steps:
[0103] The bisphenol A epoxy resin, the DOPO modified phosphorus-containing epoxy resin, the bisphenol A novolac epoxy resin, the novolac epoxy resin, the bisphenol A phosphorus-containing novolac resin, the tetrafunctional novolac epoxy resin, the solvent, the curing agent, the curing accelerator, the coupling agent and the inorganic filler are mixed and shear-ripened to obtain the adhesive for the halogen-free and antimony-free flame-retardant laminate.
[0104] In some embodiments of the present invention, the mixed solvent 1 (added according to each component), the curing agent (added according to each component), the curing accelerator and the graphene oxide are mixed and stirred until dissolved to obtain a mixture A. The stirring time may be 10-12 hours.
[0105] In some embodiments of the present invention, the mixture A is mixed with the coupling agent, the resin (added according to each component), and the mixed solvent 2 (added according to each component) to obtain a mixture B. The stirring time may be 1-2 hours.
[0106] In some embodiments of the present invention, the mixture B, the spherical alumina and the aluminum hydroxide (added according to each component) are mixed, sheared and aged to obtain the adhesive for the halogen-free and antimony-free flame-retardant laminate.
[0107] In some embodiments of the present invention, the rotation speed of the shear ripening is 900-2200 rpm, for example, 900-1100 rpm or 2000-2200 rpm.
[0108] In some embodiments of the present invention, the shear ripening temperature is 40-60°C, such as 45-50°C.
[0109] In some embodiments of the present invention, the shear ripening time is 10-12 hours.
[0110] In some embodiments of the present invention, the shear ripening process is:
[0111] First, shear aging is performed at a speed of 2000-2200rpm and a glue temperature of 40-60℃ for 4-5 hours, and then shear aging is performed at a speed of 900-1100rpm and a glue temperature of 45-50℃ for 6-7 hours (the total aging time is about 10-12 hours).
[0112] In some embodiments of the present invention, under the condition that the total aging time is about 10-12 hours, the gel time of the glue solution can reach 250-260 s.
[0113] In some embodiments of the present invention, the method for preparing the adhesive for the halogen-free and antimony-free flame-retardant laminate comprises the following steps:
[0114] (1) Mix the mixed solvent 1 (added according to each component), the curing agent (added according to each component), the curing accelerator and the flame retardant, and stir until dissolved for 10-12 hours to obtain a mixture A;
[0115] (2) Mixing the mixture A with the coupling agent, the resin (added according to each component), and the mixed solvent 2 (added according to each component), and stirring for 1-2 hours to obtain a mixture B;
[0116] (3) Under stirring conditions, the mixture B and the inorganic filler (added according to each component) are mixed, and shear-ripened for 4-5 hours at a speed of 2000-2200 rpm and a glue temperature of 40-60° C., and then shear-ripened for 6-7 hours at a speed of 900-1100 rpm and a glue temperature of 45-50° C. (the total aging time is about 10-12 hours), and finally the halogen-free and antimony-free flame-retardant laminate glue is obtained.
[0117] The present invention also provides a glue solution for halogen-free and antimony-free flame-retardant laminated boards, which is prepared by the above-mentioned preparation method.
[0118] The present invention also provides a method for preparing a prepreg for a halogen-free and antimony-free flame-retardant laminate, which comprises the following steps: coating the adhesive on a reinforcing material, and drying to obtain the prepreg.
[0119] In the present invention, the reinforcing material may be electronic grade glass fiber cloth or electronic glass fiber felt.
[0120] In the present invention, the laminated board may be a FR-4 board.
[0121] In the present invention, FR-4 can be generally divided into FR-4.0 (ordinary board) and FR-4.1 (halogen-free board).
[0122] In the present invention, the FR-4.1 board uses electronic grade glass fiber cloth, such as 7628, 2116, 1080, etc. as a reinforcing material.
[0123] In the present invention, the electronic grade glass cloth (alkali-free glass fiber cloth for printed circuit boards) is a prepreg raw material conventionally used in the art.
[0124] In some embodiments of the present invention, in the method for preparing the prepreg for the halogen-free and antimony-free flame-retardant laminate (FR-4.1), the coating equipment is a vertical glue coating machine.
[0125] In the present invention, the coating vehicle speed may be 15-20 m / min, such as 17 m / min or 16 m / min.
[0126] In the present invention, preferably, the drying temperature is 200-220°C, such as 210°C or 215°C.
[0127] In the present invention, the temperature of the glue solution may be 35-45°C, for example 40°C.
[0128] In the present invention, the resin content of the prepreg can reach 42-56%, such as 45% or 55-56%.
[0129] In the present invention, the gel time of the prepreg can reach 90-100s or 85-95s.
[0130] In the present invention, the fluidity of the prepreg can reach 20-28% or 26-32%.
[0131] In the present invention, the volatile matter of the prepreg may be ≤0.5%.
[0132] In some embodiments of the present invention, the reinforcing material is electronic grade glass cloth 7628, and the preparation process of the prepreg is:
[0133] The coating vehicle speed was 17 m / min.
[0134] The drying temperature is 210°C.
[0135] The temperature of the glue solution is 40°C.
[0136] In some embodiments of the present invention, the reinforcing material is electronic grade glass cloth 7628, and the properties of the prepreg are:
[0137] The mass content of the resin in the prepreg is 45%;
[0138] The gel time of the prepreg is 90-100s;
[0139] The fluidity of the prepreg is 20-28%;
[0140] The volatile matter of the prepreg is ≤0.5%.
[0141] In some embodiments of the present invention, the reinforcing material is electronic grade glass cloth 2116, and the preparation process of the prepreg is:
[0142] The coating vehicle speed is 16m / min;
[0143] The drying temperature is 215°C;
[0144] The temperature of the glue solution is 40°C.
[0145] In some embodiments of the present invention, the reinforcing material is electronic grade glass cloth 2116, and the properties of the prepreg are:
[0146] The mass content of the resin in the prepreg is 55-56%;
[0147] The gel time of the prepreg is 85-95s;
[0148] The fluidity of the prepreg can reach 26-32%;
[0149] The volatile matter of the prepreg is ≤0.5%.
[0150] The present invention also provides a prepreg for a halogen-free and antimony-free flame-retardant laminate, which is prepared by the method.
[0151] The present invention also provides a halogen-free antimony-free flame-retardant laminate, which comprises at least one prepreg for the halogen-free antimony-free flame-retardant laminate and a metal foil or a release film covering one or both sides of the laminated prepreg.
[0152] In some embodiments of the present invention, the metal foil is copper foil.
[0153] In some embodiments of the present invention, the metal foil clad laminate comprises, in sequence, a first copper foil layer, a semi-cured sheet whose reinforcing material is electronic grade glass cloth 2116, six semi-cured sheets whose reinforcing material is electronic grade glass cloth 7628, a semi-cured sheet whose reinforcing material is electronic grade glass cloth 2116, and a second copper foil layer.
[0154] In some embodiments of the present invention, the halogen-free and antimony-free flame-retardant laminate has a thickness of 1.42-1.58 mm, such as 1.51 mm, 1.43 mm or 1.58 mm.
[0155] In some embodiments of the present invention, the comparative tracking index CTI of the halogen-free and antimony-free flame retardant laminate is ≥ 600 V, for example 600 V.
[0156] In some embodiments of the present invention, the thermal conductivity (thermal conductivity) of the halogen-free and antimony-free flame-retardant laminate is ≥1.0 W / mK, such as 1.52 W / mK, 1.45 W / mK or 1.61 W / mK.
[0157] In some embodiments of the present invention, the peel strength of the halogen-free and antimony-free flame-retardant laminate is ≥8.0 IBS / IN, such as 10.5 IBS / IN, 9.5 IBS / IN or 10.9 IBS / IN.
[0158] In some embodiments of the present invention, the bow / warping degree of the halogen-free and antimony-free flame-retardant laminate is ≤1.0%, such as 0.1%, 0.3% or 0.2%.
[0159] In some embodiments of the present invention, the halogen-free and antimony-free flame-retardant laminate has no delamination and no blistering on the surface at 288° C. for 20 seconds.
[0160] In some embodiments of the present invention, the flame retardant grade of the halogen-free and antimony-free flame retardant laminate is UL94V0.
[0161] In some embodiments of the present invention, the glass transition temperature Tg of the halogen-free and antimony-free flame retardant laminate is ≥ 155°C, such as 160°C, 155°C or 165°C.
[0162] In some embodiments of the present invention, the thermal decomposition temperature (Td) of the halogen-free and antimony-free flame-retardant laminate is ≥325°C, such as 360°C, 355°C or 365°C.
[0163] In some embodiments of the present invention, the halogen-free and antimony-free flame-retardant laminate does not fade after being immersed in a process solvent for 60 minutes.
[0164] In some embodiments of the present invention, the antimony content of the halogen-free and antimony-free flame retardant laminate is 0 ppm.
[0165] In some embodiments of the present invention, the chlorine content of the halogen-free and antimony-free flame-retardant laminate is less than 900 PPM, such as 250 ppm, 240 ppm or 280 ppm.
[0166] In some embodiments of the present invention, the bromine content of the halogen-free and antimony-free flame-retardant laminate is less than 900 PPM, such as 20 ppm, 18 ppm or 30 ppm.
[0167] In some embodiments of the present invention, the total content of bromine and chlorine in the halogen-free and antimony-free flame-retardant laminate is less than 1500 PPM, such as 270 ppm, 258 ppm or 310 ppm.
[0168] The present invention also provides a method for preparing the halogen-free and antimony-free flame-retardant laminate, which comprises the following steps:
[0169] Lamination: Laminating a plurality of the halogen-free and antimony-free flame-retardant laminates with prepregs, and covering the upper and lower surfaces with metal foil or release film to obtain a semi-finished plate;
[0170] ② The semi-finished plate is subjected to hot pressing and vacuum pressing to obtain the semi-finished plate.
[0171] In the present invention, the preparation method of the semi-finished plate material can be: the semi-finished plate material is formed by a plurality of intermediate prepregs, upper and lower copper foils / release films, upper and lower steel plates, and 18 upper and lower kraft papers.
[0172] In the present invention, no pressure is required when stacking, and the stacking requirements generally follow the four major principles in this field: the principle of matching high and low glue content, the principle of consistent layout, the principle of structural symmetry, and the principle of left and right matching.
[0173] In the present invention, different electronic glass fiber cloths can be selected according to different thicknesses, such as 8 7628 electronic glass fiber cloth semi-cured sheets are used for 1.5mm thick plates; 2*7628+2*1506+2*7628 are used for 1.1mm thick plates; and 2*7628+1*2116+2*7628 are used for 0.9mm thick plates.
[0174] In step ②, the pressing method and conditions can be conventional methods and conditions in the art, such as hot pressing and vacuum segmented pressing. Ensure that the sheet is cooled gradually to avoid direct pressure release after hot pressing, which will cause large internal stress of the sheet, and increase cold pressing to reduce sheet warping.
[0175] In the present invention, the vacuum value of the hot-pressing vacuum pressing may be 740-800 mmHg, more preferably 760 mmHg.
[0176] In the present invention, the hot pressing and vacuum pressing can be carried out in stages, such as stage one, stage two, and stage three.
[0177] In the present invention, the first stage can be: the vacuum value is 740-760 mmHg, the temperature at the start of hot pressing is 110-130°C, and the pressure at the start of hot pressing is 5-10 kg / cm 2 The temperature at the end of hot pressing is 200-220℃, and the pressure at the end of hot pressing is 25-30 kg / cm 2 The hot pressing time is 50-60min.
[0178] In the present invention, the second stage can be: the vacuum value is 740-760 mmHg, the temperature of hot pressing is 200-220°C, and the pressure of hot pressing is divided into initial pressure, intermediate pressure and late pressure; the initial pressure is 25-30 kg / cm 2 The initial pressure pressing time is 10-15 min; the intermediate pressure is 35-40 kg / cm 2 The mid-term pressure pressing time is 35-40 min; the late pressure is 20-25kg / cm 2 The time of the later pressure pressing is 10-15 min.
[0179] In the present invention, the third stage can be: vacuum or non-vacuum conditions, the temperature at the start of hot pressing is 200-220°C, and the pressure at the start of hot pressing is 20-25 kg / cm 2 The temperature at the end of hot pressing is 110-130℃, and the pressure at the end of hot pressing is 30-35kg / cm 2 The hot pressing time is 20-40min.
[0180] In the present invention, after the pressing, subsequent shape processing and inspection processes are generally performed to ensure the quality of the product.
[0181] In the present invention, the term “comparative tracking index” (CTI) is referred to as CTI for short.
[0182] In the present invention, the term “glass transition temperature” (TG) is abbreviated as TG.
[0183] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0184] The reagents and raw materials used in the present invention are commercially available.
[0185] The positive and progressive effects of the present invention are:
[0186] 1. The semi-cured sheet prepared by the adhesive of the present invention, and the flame-retardant laminate (such as FR-4.1) further prepared have the advantages of high thermal conductivity, CTI ≥ 600 V, TG ≥ 155 ° C, and halogen-free and antimony-free. The preparation method of the adhesive in the present invention is simple, low in cost, stable in technology, low in defect rate, strong in process controllability, and suitable for mass production.
[0187] 2. The high thermal conductivity, CTI ≥ 600 V, TG ≥ 155 ° C, halogen-free and antimony-free flame-retardant laminate (FR-4.1) of the present invention meets the production process of the downstream printed circuit board (PCB) for the board, and has good comprehensive performance, especially halogen-free, thermal conductivity, CTI, flame retardant, TG, and thickness uniformity. For example, the bromine content (ppm) is less than 500ppm, which is far lower than the industry standard value (bromine content <900ppm); the thermal conductivity coefficient is high. The high thermal conductivity, CTI ≥ 600 V, TG ≥ 155 ° C, halogen-free and antimony-free flame-retardant laminate (FR-4.1) of the present invention does not delaminate or bubble in the thermal stress test.
[0188] 3. The present invention adopts a combination of multiple resins, and selects resins with lower costs in the industry, such as bisphenol A epoxy resin (such as NPEL128 produced by Kunshan Nan Ya), which reduces costs while ensuring the performance of the board. Specifically:
[0189] High TG: The rigid structure and the groups that are beneficial to increase the cross-linking density are introduced, which can achieve TG: 155-165℃;
[0190] Good thermal stability: mixed resin, high and low molecular weight, increased cross-linking density;
[0191] Excellent flame retardancy: The introduction of phosphorus, nitrogen, inorganic fillers (such as graphene oxide), etc. can effectively exert flame retardant effects in the system;
[0192] It has good compatibility and chemical stability, good fluidity and wettability, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0193] Figure 1Schematic diagram of the structure of the copper clad laminate in Example 3. DETAILED DESCRIPTION
[0194] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0195] In the following examples and comparative examples, the sources and descriptions of the raw materials are as follows:
[0196] DMF: N,N-dimethylformamide;
[0197] ETOH: ethanol;
[0198] DMSO: dimethyl sulfoxide;
[0199] GBL: gamma-butyrolactone;
[0200] DICY: dicyandiamide;
[0201] DDS: 4,4'-diaminodiphenyl sulfone;
[0202] Diphenylimidazole: 2-Phenylimidazole;
[0203] Graphene oxide: thickness is 0.8nm-1.2nm, single layer, specific surface area is 500m² / g-1000m² / g, carbon-oxygen ratio is between 2-4;
[0204] Silane coupling agent KH-570: γ-methacryloxypropyltrimethoxysilane;
[0205] Bisphenol A epoxy resin: NPEL128E produced by Kunshan Nan Ya, solid content 100%, epoxy equivalent 185-190g / eq, viscosity 12000-15000mPa·s at 25°C;
[0206] DOPO-type modified phosphorus-containing epoxy resin: DFE202 produced by Sichuan Dongcai, with a solid content of 75%, epoxy equivalent of 295-335g / eq, and a phosphorus content of 3.1-3.2%;
[0207] Bisphenol A novolac epoxy resin: SQAN-201EK80 produced by Shengquan, solid content 80%, epoxy equivalent 190-220g / eq;
[0208] Phenolic epoxy resin: DEN438 EK85J produced by Dow, solid content 85%, viscosity 600-1600 mPa.s / 25℃, epoxy equivalent 176-181g / eq;
[0209] Bisphenol A type phosphorus-containing phenolic resin: XZ92741 produced by Dow, solid content 56-58%, viscosity 500-2500mPa.s / 25℃, phosphorus content 9-10%;
[0210] Tetrafunctional phenolic epoxy resin: NPPN431A70 produced by Kunshan Nan Ya, solid content 70%, epoxy equivalent 200-220g / eq, softening point: 82-92℃;
[0211] PM: propylene glycol methyl ether;
[0212] EA: ethyl acetate;
[0213] IPA: isopropyl alcohol;
[0214] Spherical alumina: SLA-5, D50 particle size is 5±1μm, D90 particle size is 15±3μm;
[0215] Aluminum hydroxide: MARTINAL® OL-104LEO, purity ≥99.6%, whiteness ≥93, particle size range: D50, 1.9±0.2μm; D90, 3.2±1.0μm; oil absorption rate: 27-32 ml / 100g; conductivity (10%, in water): 20μS / cm;
[0216] GEBR573K70 resin: purchased from Hongchang Electronic Materials Co., Ltd.;
[0217] YN3570K70 resin: purchased from Jiangsu Yangnong Jinhu Chemical Co., Ltd.;
[0218] 2-Methylimidazole: Its chemical name is 2-Methylimidezale, abbreviated as 2-MI.
[0219] Gel time test method:
[0220] (1) Crumble the resin of the prepreg into resin powder and place it on clean kraft paper.
[0221] (2) Collect the powder and place it through a 100-mesh sieve to sift out the fine powder, not less than 200 mg.
[0222] (3) Start the gel time tester and stabilize the temperature between the hot plates at 171±2℃.
[0223] (4) Clean the hot plate, use a small spoon to take 85~100 mg of powder and put it into the hot plate, and start the timer at the same time. When the gel system reaches 10 seconds, use a toothpick to stir it evenly. After a certain period of time, gently pull the sample. If the sample breaks, stop the timer. The timer reading at this time is the gel time.
[0224] Test method for resin fluidity:
[0225] (1) Cut four (4 ± 0.02) inch × (4 ± 0.02) inch square specimens on a square die punch. The specimens should be cut 3 mm away from the edge of the material.
[0226] (2) Use an electronic balance to weigh the total weight W1 of the four samples to an accuracy of 0.01g.
[0227] (3) Stack the four specimens neatly and sandwich them between two release films.
[0228] (4) The sandwich consisting of the sample, release film and steel plate is placed in a flow press to press the laminate.
[0229] (5) Pressing parameters are: temperature 171±5℃, pressure 0.45±0.03MPa, setting time 7min.
[0230] (6) Take out the pressed laminate and remove the release film.
[0231] (7) Use a round die punch to punch a disc with a diameter of 3.192 ± 0.02 inches in the center of the laminate.
[0232] (8) Use an electronic balance to weigh the disc, W2.
[0233] (9) Calculation: Fluidity (%) = [(W1-W2×2) / W1] × 100%.
[0234] Testing method for volatile matter content:
[0235] (1) On a square die punch, cut square specimens of (4 ± 0.02) inches × (4 ± 0.02) inches or (101.6 mm × 101.6 mm) (three pieces from the left, middle, and right sides of each specimen). Punch a small hole with a diameter of about 1 / 8 mm in the corner of the specimen. The specimen cannot be cut within 10 mm from the edge of the material.
[0236] (2) Weigh the sample to an accuracy of 0.001 g and record the weight W1.
[0237] (3) Use a paper clip to pass through the small hole of the sample and hang it under the shelf of the oven.
[0238] (4) Place the rack with the sample in an oven at 163±4℃ for 15±1min.
[0239] (5) Take the sample out of the oven and weigh it within 2 minutes to an accuracy of 0.001 g, and record the weight W2.
[0240] (6) Calculate the volatile matter content (%) = [(W1-W2) / W1] × 100%.
[0241] The detection method of comparative tracking index is: the highest voltage value that the material surface can withstand 50 drops of electrolyte without forming leakage traces.
[0242] The test method for thermal conductivity (thermal conductivity) is: ASTM D5470.
[0243] The test method for peel strength is: DIN 53273.
[0244] The method for detecting bow / warpage is to ensure that the four corners of the copper clad board are completely in contact with the plane. Then, measure the distance between the highest point in the middle and the plane. The calculation formula is: Warpage = (highest point distance / PCB board long side length) * 100%.
[0245] The test method for glass transition temperature (Tg) is: E2 / 105 DSC IPC-TM-650 2.4.25.
[0246] The detection method of thermal decomposition temperature (Td) is: 10C / min, N, 5%WtLoss.
[0247] The test method for chemical resistance (process solvent immersion method) is: no fading for 60 minutes.
[0248] The detection method for antimony and halogen content is: IEC61249-2-21.
[0249] Example 1
[0250] The raw material formula of the adhesive solution for halogen-free and antimony-free flame retardant laminate (FR-4.1) is shown in Table 1.
[0251] Table 1 Raw material formula
[0252]
[0253] Note: Mixed solvent 1 refers to: DMF (N,N-dimethylformamide), ethanol, dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL) mixed in a mass ratio of 5:3:1:1;
[0254] The mixed solvent 2 is a mixture of PM (propylene glycol methyl ether), ethyl acetate and isopropanol in a mass ratio of 5:3:2.
[0255] The method for manufacturing the adhesive solution of the halogen-free and antimony-free flame-retardant laminate (FR-4.1) specifically comprises the following steps:
[0256] (1) Mix the mixed solvent 1 (added according to each component), the curing agent (added according to each component), the curing accelerator and the flame retardant, and stir until dissolved for 10-12 hours to obtain a mixture A;
[0257] (2) Mixing the mixture A with the coupling agent, the resin (added according to each component), and the mixed solvent 2 (added according to each component), and stirring for 1-2 hours to obtain a mixture B;
[0258] (3) Under stirring conditions, the mixture B and the inorganic filler (added according to each component) are mixed, and shear-ripened at a speed of 2200 rpm and a temperature of 50° C. for 5 hours, and then shear-ripened at a speed of 1100 rpm and a temperature of 50° C. for 7 hours (total aging time is about 12 hours), and finally a halogen-free and antimony-free flame-retardant laminate adhesive is obtained. Under the condition of a total aging time of about 10-12 hours, the gel time of the adhesive is 250-260 s.
[0259] When observing mixture A under a polarizing microscope at 40x (total magnification), there were less than 3 DICY crystals in any field of view.
[0260] Example 2
[0261] This embodiment provides a method for preparing a prepreg for a halogen-free and antimony-free flame-retardant laminate (FR-4.1), which comprises the following steps:
[0262] The electronic grade glass fiber cloth is coated with the adhesive solution described in Example 1, and then dried to obtain the product.
[0263] The electronic grade glass cloth (alkali-free glass fiber cloth for printed circuit boards) is a prepreg raw material conventionally used in the art, such as electronic grade glass cloth 7628 or electronic grade glass cloth 2116.
[0264] In the method for preparing the prepreg for the halogen-free and antimony-free flame-retardant laminate (FR-4.1), the coating equipment is a vertical glue coating machine.
[0265] (1) Prepreg produced from electronic grade glass cloth 7628:
[0266] The coating vehicle speed was 17 m / min.
[0267] The drying temperature is 210°C.
[0268] The temperature of the glue solution is 40°C.
[0269] The mass content of the resin in the prepreg can reach 45%.
[0270] The gel time of the prepreg can reach 90-100 s (the gel time of the glue solution can reach 250-260 s).
[0271] The fluidity of the prepreg can reach 20-28%.
[0272] The volatile matter of the prepreg is ≤0.5%.
[0273] (2) Prepreg produced from electronic grade glass cloth 2116:
[0274] The coating vehicle speed was 16 m / min.
[0275] The drying temperature is 215°C.
[0276] The temperature of the glue solution is 40°C.
[0277] The mass content of the resin in the prepreg is 55-56%.
[0278] The gel time of the prepreg can reach 85-95 s (the gel time of the glue solution can reach 250-260 s).
[0279] The fluidity of the prepreg can reach 26-32%.
[0280] The volatile matter of the prepreg is ≤0.5%.
[0281] Example 3
[0282] This embodiment provides a method for preparing a halogen-free and antimony-free flame-retardant laminate (FR-4.1), which comprises the following steps:
[0283] Lamination: 8 sheets of prepregs (1*2116+6*7628+1*2116) prepared in Example 2 are stacked and covered with copper foil on both the upper and lower surfaces to obtain a semi-finished plate. The semi-finished product is formed by 8 prepregs in the middle, upper and lower copper foils, upper and lower steel plates, and 18 pieces of kraft paper on the upper and lower surfaces;
[0284] ② The semi-finished product is subjected to hot pressing and vacuum pressing to obtain a product having a structure as follows: Figure 1 shown.
[0285] No pressure is required when stacking. Stacking requires following four principles: the principle of matching high and low glue content, the principle of consistent layout, the principle of structural symmetry, and the principle of left and right matching.
[0286] In step ②, the pressing method is hot pressing and vacuum segmented pressing. Ensure that the plate is cooled gradually to avoid direct pressure release after hot pressing, which will cause large internal stress of the plate, and increase cold pressing to reduce plate warping.
[0287] The hot pressing vacuum value is 750 mmHg.
[0288] Stage 1: Start to evacuate until the hot pressing vacuum value reaches 750 mmHg, and maintain it at 740-750 mmHg. Hot pressing temperature: 120-210℃ (this temperature range indicates a linear increase from 120℃ to 210℃), hot pressing pressure: 5-25 kg / cm2 (This pressure range represents from 5 kg / cm 2 Linear pressure increase to 25 kg / cm 2 ), hot pressing time: 55min. The heating and pressure increase are completed during the entire pressing process, that is, the pressure increase and heating time is 55min, the starting temperature of the hot pressing is 120℃, and the hot pressing pressure is 5 kg / cm 2 The hot pressing end point temperature is 210℃ and the hot pressing pressure is 25 kg / cm 2 That is, the heating rate of hot pressing is 1.63℃ / min, and the pressure increase rate of hot pressing is 0.36 kg / cm 2 / min.
[0289] Stage 2: Continuously evacuate to ensure that the hot pressing vacuum value is 740-750 mmHg, hot pressing temperature: 210℃, hot pressing pressure is divided into initial pressure, mid-term pressure and late pressure, among which: the initial pressure is 25 kg / cm 2 The hot pressing time is 10 min, and the medium pressure is 35 kg / cm 2 The hot pressing time is 35 min, and the later pressure is 20 kg / cm 2 , Hot pressing time: 15min.
[0290] Stage 3: Stop vacuuming, hot pressing temperature: 210-120℃ (this temperature range represents a linear temperature drop from 210℃ to 120℃), hot pressing pressure: 20-30 kg / cm 2 (This pressure range represents from 20 kg / cm 2 Linear pressure increase to 30 kg / cm 2 ), hot pressing time: 30min. Cooling and pressing are completed during the whole pressing process, that is, the time of pressing and cooling is 30min, the starting temperature of hot pressing is 210℃, and the hot pressing pressure is 20 kg / cm 2 The hot pressing end point temperature is 120℃ and the hot pressing pressure is 30 kg / cm 2 That is, the cooling rate of hot pressing is 3.00℃ / min, and the pressure increase rate of hot pressing is 0.33 kg / cm 2 / min.
[0291] Effect Example 1
[0292] The copper clad laminate obtained in Example 3 was subjected to performance testing, and the results are shown in Table 2.
[0293] Table 2 Performance parameters of copper clad laminate in Example 3
[0294]
[0295] Comparative Example 1
[0296] (1) The raw material formula of the laminate (FR-4.1) adhesive is shown in Table 3.
[0297] Table 3
[0298]
[0299] The manufacturing method of the glue solution specifically comprises the following steps:
[0300] Under stirring conditions, GEBR573K70 resin, DICY, 2-MI and butanone were mixed in the proportions shown in Table 3, and shear-ripened at a speed of 2200 rpm and a glue temperature of 50°C for 5 hours, and then shear-ripened at a speed of 1100 rpm and a glue temperature of 50°C for 7 hours (the total aging time was about 12 hours), and finally a halogen-free and antimony-free flame-retardant laminate glue was obtained.
[0301] (2) The preparation method of the prepreg for the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Comparative Example 1 is the same as that in Example 2.
[0302] The resin content of the prepreg can reach 45%.
[0303] The gel time of the prepreg can reach 75~105s (the gel time of the glue can reach 250~320s).
[0304] (3) The preparation method of the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Comparative Example 1 is the same as that in Example 3.
[0305] The pressing method described in step ② is hot pressing and vacuum pressing. Ensure that the plate is cooled gradually to avoid direct pressure release after hot pressing, which will cause large internal stress of the plate. Increase cold pressing to reduce plate warping.
[0306] The hot pressing vacuum value is 750 mmHg.
[0307] The hot pressing conditions are: 175-180°C, pressure: 35 kg / cm 2 , hot pressing time: 120-180min.
[0308] (4) The properties of the copper clad laminate obtained in step (3) were measured. The results are shown in Table 4.
[0309] Table 4 Performance parameters of copper clad laminate in comparative example 1
[0310]
[0311] Comparative Example 2
[0312] (1) The raw material formula of the laminate (FR-4.1) adhesive is shown in Table 5.
[0313] Table 5
[0314]
[0315] The manufacturing method of the glue solution specifically comprises the following steps:
[0316] Under stirring conditions, YN3570K70 resin, DICY, 2-MI and butanone were mixed in the proportions shown in Table 5, and shear-ripened for 5 hours at a speed of 2200 rpm and a glue temperature of 50°C, and then shear-ripened for 7 hours at a speed of 1100 rpm and a glue temperature of 50°C (the total aging time was about 12 hours), and finally a halogen-free and antimony-free flame-retardant laminate glue was obtained.
[0317] (2) The preparation method of the prepreg for the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Comparative Example 2 is the same as that in Example 2.
[0318] The resin content of the prepreg can reach 45%.
[0319] The gel time of the prepreg can reach 80~110s (the gel time of the glue solution can reach 235~255s).
[0320] (3) The preparation method of the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Comparative Example 1 is the same as that in Example 3.
[0321] The pressing method described in step ② is hot pressing and vacuum pressing. Ensure that the plate is cooled gradually to avoid direct pressure release after hot pressing, which will cause large internal stress of the plate. Increase cold pressing to reduce plate warping.
[0322] The hot pressing vacuum value is 750 mmHg.
[0323] The hot pressing conditions are: 175-180°C, pressure: 35 kg / cm 2 , hot pressing time: 120-180min.
[0324] (4) The properties of the copper clad laminate obtained in step (3) were measured. The results are shown in Table 6.
[0325] Table 6 Performance parameters of copper clad laminate in comparative example 2
[0326]
[0327] Comparative Example 3
[0328] (1) The raw material formula of the laminate (FR-4.1) adhesive is shown in Table 7 below.
[0329] Table 7
[0330]
[0331] Note: Mixed solvent 1 refers to: DMF (N,N-dimethylformamide), ethanol, dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL) mixed in a mass ratio of 5:3:1:1;
[0332] The mixed solvent 2 is a mixture of PM, ethyl acetate and isopropanol in a mass ratio of 5:3:2.
[0333] The preparation method of the glue solution is the same as that of Example 1.
[0334] (2) The preparation method of the prepreg for the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Comparative Example 3 is the same as that in Example 2.
[0335] (3) The preparation method of the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Comparative Example 3 is the same as that in Example 3.
[0336] (4) The properties of the copper clad laminate obtained in step (3) were measured. The results are shown in Table 8.
[0337] Table 8 Performance parameters of copper clad laminate in comparative example 3
[0338]
[0339] Comparative Example 4
[0340] (1) The raw material formula of the laminate (FR-4.1) adhesive is shown in Table 9 below.
[0341] Table 9
[0342]
[0343] Note: Mixed solvent 1 refers to a mixture of DMF, ethanol, dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL) in a mass ratio of 5:3:1:1;
[0344] The mixed solvent 2 is a mixture of PM, ethyl acetate and isopropanol in a mass ratio of 5:3:2.
[0345] The preparation method of the glue solution is the same as that of Example 1.
[0346] (2) The preparation method of the prepreg for the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Comparative Example 4 is the same as that in Example 2.
[0347] (3) The preparation method of the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Comparative Example 4 is the same as that in Example 3.
[0348] (4) The properties of the copper clad laminate obtained in step (3) were measured. The results are shown in Table 10.
[0349] Table 10 Performance parameters of copper clad laminate in comparative example 4
[0350]
[0351] Example 4
[0352] (1) The raw material formula of the laminate (FR-4.1) adhesive is shown in Table 11 below.
[0353] Table 11
[0354]
[0355] Note: Mixed solvent 1 refers to a mixture of DMF, ethanol, dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL) in a mass ratio of 5:3:1:1;
[0356] The mixed solvent 2 is a mixture of PM, ethyl acetate and isopropanol in a mass ratio of 5:3:2.
[0357] The preparation method of the glue solution is the same as that of Example 1.
[0358] (2) The method for preparing the prepreg for the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Example 4 is the same as that in Example 2.
[0359] (3) The preparation method of the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Example 4 is the same as that in Example 3.
[0360] (4) The properties of the copper clad laminate obtained in step (3) were measured. The results are shown in Table 12.
[0361] Table 12 Performance parameters of copper clad laminate in Example 4
[0362]
[0363] Example 5
[0364] (1) The raw material formula of the laminate (FR-4.1) adhesive is shown in Table 13 below.
[0365] Table 13
[0366]
[0367] Note: Mixed solvent 1 refers to a mixture of DMF, ethanol, dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL) in a mass ratio of 5:3:1:1;
[0368] The mixed solvent 2 is a mixture of PM, ethyl acetate and isopropanol in a mass ratio of 5:3:2.
[0369] The preparation method of the glue solution is the same as that of Example 1.
[0370] (2) The method for preparing the prepreg for the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Example 5 is the same as that in Example 2.
[0371] (3) The preparation method of the halogen-free and antimony-free flame-retardant laminate (FR-4.1) in Example 5 is the same as that in Example 3.
[0372] (4) The properties of the copper clad laminate obtained in step (3) were measured. The results are shown in Table 14.
[0373] Table 14 Performance parameters of copper clad laminate in Example 5
[0374]
[0375] According to Examples 3, 4 and 5, the prepreg prepared by the adhesive of the present invention and the flame retardant laminate (eg FR-4.1) further prepared have the advantages of high thermal conductivity, CTI≥600 V, TG≥155°C, and no halogen or antimony.
Claims
1. A resin composition, characterized in that By mass, it includes the following components: 360-440 parts of bisphenol A epoxy resin, wherein the bisphenol A epoxy resin has an epoxy equivalent of 185-190 g / eq and a viscosity of 12000-15000 mPa·s at 25° C.; 1260-1540 parts of a DOPO type modified phosphorus-containing epoxy resin, wherein the DOPO type modified phosphorus-containing epoxy resin has an epoxy equivalent of 295-335 g / eq; 180-220 parts of bisphenol A novolac epoxy resin, wherein the epoxy equivalent of the bisphenol A novolac epoxy resin is 190-220 g / eq; 90-110 parts of a novolac epoxy resin, wherein the novolac epoxy resin has an epoxy equivalent of 176-181 g / eq; 270-330 parts of bisphenol A type phosphorus-containing phenolic resin, wherein the viscosity of the bisphenol A type phosphorus-containing phenolic resin at 25° C. is 500-2500 mPa.s; 90-110 parts of a tetrafunctional novolac epoxy resin, wherein the epoxy equivalent of the tetrafunctional novolac epoxy resin is 200-220 g / eq.
2. The resin composition according to claim 1, characterized in that The resin composition satisfies one or more of the following conditions: (1) The bisphenol A epoxy resin is NPEL128E produced by Kunshan Nan Ya; (2) The solid content of the bisphenol A epoxy resin is 100%; (3) The mass fraction of the bisphenol A epoxy resin is 400 parts; (4) The DOPO-type modified phosphorus-containing epoxy resin is DFE202 produced by Sichuan Dongcai; (5) The solid content of the DOPO type modified phosphorus-containing epoxy resin is 70-80%, for example 75%; (6) The phosphorus content of the DOPO type modified phosphorus-containing epoxy resin is 3.1-3.2%; (7) The mass fraction of the DOPO type modified phosphorus-containing epoxy resin is 1400 parts; (8) The bisphenol A novolac epoxy resin is SQAN-201EK80 produced by Shengquan; (9) The solid content of the bisphenol A novolac epoxy resin is 75-85%, for example 80%; (10) The mass fraction of the bisphenol A novolac epoxy resin is 200 parts; (11) The phenolic epoxy resin is DEN438 EK85J phenolic epoxy resin produced by Dow Chemical; (12) The solid content of the phenolic epoxy resin is 80-90%, for example 85%; (13) The viscosity of the phenolic epoxy resin at 25°C is 600-1600 mPa.s; (14) The mass fraction of the phenolic epoxy resin is 100 parts; (15) The bisphenol A type phosphorus-containing phenolic resin is XZ92741 produced by Dow; (16) The solid content of the bisphenol A type phosphorus-containing phenolic resin is 56-58%; (17) The phosphorus content of the bisphenol A type phosphorus-containing phenolic resin is 9-10%; (18) The mass fraction of the bisphenol A type phosphorus-containing phenolic resin is 300 parts; (19) The tetrafunctional phenolic epoxy resin is NPPN431A70 produced by Kunshan Nan Ya; (20) The solid content of the tetrafunctional phenolic epoxy resin is 65-75%, for example 70%; (21) The softening point of the tetrafunctional phenolic epoxy resin is 82-92°C; The mass fraction of the tetrafunctional phenolic epoxy resin described in (22) is 100 parts; Preferably, the mass ratio of the bisphenol A epoxy resin, the DOPO modified phosphorus-containing epoxy resin, the bisphenol A novolac epoxy resin, the novolac epoxy resin, the bisphenol A phosphorus-containing novolac resin, and the tetrafunctional novolac epoxy resin is 4:14:2:1:3:
1.
3. A raw material composition of adhesive for halogen-free and antimony-free flame-retardant laminates, characterized in that: By mass, it includes the following components: 360-440 parts of bisphenol A epoxy resin, wherein the bisphenol A epoxy resin has an epoxy equivalent of 185-190 g / eq and a viscosity of 12000-15000 mPa·s at 25° C.; 1260-1540 parts of a DOPO type modified phosphorus-containing epoxy resin, wherein the DOPO type modified phosphorus-containing epoxy resin has an epoxy equivalent of 295-335 g / eq; 180-220 parts of bisphenol A novolac epoxy resin, wherein the epoxy equivalent of the bisphenol A novolac epoxy resin is 190-220 g / eq; 90-110 parts of a novolac epoxy resin, wherein the novolac epoxy resin has an epoxy equivalent of 176-181 g / eq; 270-330 parts of bisphenol A type phosphorus-containing phenolic resin, wherein the viscosity of the bisphenol A type phosphorus-containing phenolic resin at 25° C. is 500-2500 mPa.s; 90-110 parts of a tetrafunctional novolac epoxy resin, wherein the epoxy equivalent of the tetrafunctional novolac epoxy resin is 200-220 g / eq; Solvents; 72-88 parts of curing agent; 0.5-1.5 parts of curing accelerator; 18-22 parts of silane coupling agent; Optionally, the raw material composition further comprises an inorganic filler.
4. The raw material composition of the adhesive for halogen-free and antimony-free flame-retardant laminated board according to claim 3, characterized in that: The raw material composition of the adhesive for the halogen-free antimony flame-retardant laminate meets one or more of the following conditions: (1) The bisphenol A epoxy resin is the bisphenol A epoxy resin as claimed in claim 2; (2) The solvent includes a mixed solvent 1 and a mixed solvent 2, wherein the mixed solvent 1 is a solvent that can dissolve the curing agent, the curing accelerator and part of the inorganic filler, and the mixed solvent 2 is a solvent that can dissolve the coupling agent, the bisphenol A type epoxy resin, the DOPO type modified phosphorus-containing epoxy resin, the bisphenol A novolac epoxy resin, the novolac epoxy resin, the bisphenol A type phosphorus-containing novolac resin, and the tetrafunctional novolac epoxy resin; Preferably, the mixed solvent 1 comprises DMF, ethanol, dimethyl sulfoxide, and γ-butyrolactone, and the mass ratio of DMF, ethanol, dimethyl sulfoxide, and γ-butyrolactone may be 5:3:1:1; Preferably, the mixed solvent 2 comprises PM, ethyl acetate and isopropanol, and the mass ratio of PM, ethyl acetate and isopropanol may be 5:3:2; Preferably, the mass fraction of the mixed solvent 1 is 450-550 parts, for example, 500 parts; Preferably, the mass fraction of the mixed solvent 2 is 135-165 parts, for example 150 parts; (3) The mass fraction of the curing agent is 80 parts; (4) The curing agent is 4,4'-diaminodiphenyl sulfone and / or dicyandiamide; (5) The mass fraction of the dicyandiamide is 45-55 parts, for example, 50 parts; (6) The mass fraction of the 4,4'-diaminodiphenyl sulfone is 27-33 parts, for example, 30 parts; (7) The curing accelerator is diphenylimidazole; (8) The mass fraction of the curing accelerator is 0.9-1.1 parts, for example, 1.0 parts; (9) The silane coupling agent is KH-570; (10) The mass fraction of the silane coupling agent is 20 parts; (11) The inorganic filler includes graphene oxide; Preferably, the mass fraction of the graphene oxide is 45-55 parts, for example 50 parts; Preferably, the graphene oxide is a single layer; Preferably, the thickness of the graphene oxide is 0.8nm-1.2nm; Preferably, the specific surface area of the graphene oxide is 500m² / g-1000m² / g; Preferably, the carbon-oxygen ratio of the graphene oxide is between 2 and 4; (12) The inorganic filler also includes spherical aluminum oxide and / or aluminum hydroxide; Preferably, the sum of the mass fractions of the spherical alumina and / or aluminum hydroxide is 1080-1320 parts, for example 1200 parts; Preferably, the mass fraction of the aluminum hydroxide is 900-1100 parts, for example 1000 parts; Preferably, the grade of the aluminum hydroxide is MARTINAL® OL-104LEO; Preferably, the purity of the aluminum hydroxide is ≥99.6% and the whiteness is ≥93; Preferably, the particle size range of the aluminum hydroxide is: D50, 1.9±0.2 μm; D90, 3.2±1.0 μm; Preferably, the oil absorption rate of the aluminum hydroxide is: 27-32 ml / 100g; Preferably, the conductivity of the aluminum hydroxide is: in water, the mass concentration of aluminum hydroxide is 10%, 20 μS / cm; Preferably, the mass fraction of the spherical alumina is 180-220 parts, for example 200 parts; Preferably, the grade of the spherical alumina is SLA-5; Preferably, the D50 particle size of the spherical alumina is 5±1 μm; Preferably, the D90 particle size of the spherical alumina is 15±3 μm; (13) The mass fraction of the inorganic filler is 1125-1375 parts, for example, 1250 parts; (14) The DOPO type modified phosphorus-containing epoxy resin is the DOPO type modified phosphorus-containing epoxy resin as claimed in claim 2; (15) The bisphenol A novolac epoxy resin is the bisphenol A novolac epoxy resin as claimed in claim 2; (16) The phenolic epoxy resin is the phenolic epoxy resin as claimed in claim 2; (17) The bisphenol A type phosphorus-containing phenolic resin is the bisphenol A type phosphorus-containing phenolic resin as claimed in claim 2; And the tetrafunctional phenolic epoxy resin described in (18) is the tetrafunctional phenolic epoxy resin described in claim 2.
5. A method for preparing a halogen-free and antimony-free flame-retardant adhesive for laminated boards, characterized in that: It includes the following steps: The bisphenol A epoxy resin as claimed in claim 3 or 4, the DOPO modified phosphorus-containing epoxy resin, the bisphenol A novolac epoxy resin, the novolac epoxy resin, the bisphenol A phosphorus-containing novolac resin, the tetrafunctional novolac epoxy resin, the solvent, the curing agent, the curing accelerator, the coupling agent, and the inorganic filler are mixed, sheared and aged to obtain the adhesive for the halogen-free and antimony-free flame-retardant laminate; Preferably, the mixed solvent 1, the curing agent, the curing accelerator and the graphene oxide are mixed and stirred until dissolved to obtain a mixture A; Preferably, the mixture A is mixed with the coupling agent, the bisphenol A epoxy resin, the DOPO modified phosphorus-containing epoxy resin, the bisphenol A novolac epoxy resin, the novolac epoxy resin, the bisphenol A phosphorus-containing novolac resin, the tetrafunctional novolac epoxy resin, and the mixed solvent 2 to obtain a mixture B; Preferably, the mixture B, the spherical aluminum oxide and the aluminum hydroxide are mixed, sheared and aged to obtain the adhesive for the halogen-free and antimony-free flame-retardant laminated board; Preferably, the rotation speed of the shear ripening is 900-2200 rpm, such as 900-1100 rpm or 2000-2200 rpm; Preferably, the shear ripening temperature is 40-60°C, such as 45-50°C; Preferably, the shearing and ripening time is 10-12 hours; Preferably, the shear aging process is: firstly shear aging at a speed of 2000-2200 rpm and a glue temperature of 40-60° C. for 4-5 hours, and then shear aging at a speed of 900-1100 rpm and a glue temperature of 45-50° C. for 6-7 hours.
6. A halogen-free and antimony-free flame-retardant adhesive for laminated boards, characterized in that: The invention is prepared by the method for preparing the adhesive for halogen-free and antimony-free flame-retardant laminated boards as claimed in claim 5.
7. A method for preparing a prepreg for a halogen-free and antimony-free flame-retardant laminate, characterized in that: The method comprises the following steps: coating the adhesive solution for halogen-free and antimony-free flame-retardant laminated board as claimed in claim 6 on the reinforcing material, and drying the adhesive solution; The reinforcing material may be electronic grade glass fiber cloth or electronic glass fiber felt; The coating equipment may be a vertical gluing machine; The coating vehicle speed may be 15-20 m / min, such as 17 m / min or 16 m / min; The drying temperature may be 200-220°C, for example 210°C or 215°C; The temperature of the glue solution may be 35-45°C, for example 40°C; The resin content of the prepreg may be 42-56%, such as 45% or 55-56%; The gel time of the prepreg can reach 90-100s or 85-95s; The fluidity of the prepreg can reach 20-28% or 26-32%; The volatile matter of the prepreg may be ≤0.5%.
8. A prepreg for a halogen-free and antimony-free flame-retardant laminate, characterized in that: The semi-cured sheet is prepared by the method for preparing the halogen-free and antimony-free flame-retardant laminate according to claim 7.
9. A halogen-free and antimony-free flame-retardant laminate, characterized in that: The halogen-free and antimony-free flame-retardant laminate comprises at least one prepreg for the halogen-free and antimony-free flame-retardant laminate according to claim 8 and a metal foil or a release film covering one or both sides of the laminated prepreg; The metal foil may be a copper foil; The halogen-free and antimony-free flame-retardant laminate may have a sheet thickness of 1.42-1.58 mm, such as 1.51 mm, 1.43 mm or 1.58 mm; The comparative tracking index CTI of the halogen-free and antimony-free flame-retardant laminate may be ≥600 V, for example 600 V; The thermal conductivity of the halogen-free and antimony-free flame-retardant laminate may be ≥1.0 W / mK, such as 1.52 W / mK, 1.45 W / mK or 1.61 W / mK; The peel strength of the halogen-free and antimony-free flame-retardant laminate may be ≥8.0 IBS / IN, such as 10.5 IBS / IN, 9.5 IBS / IN or 10.9 IBS / IN; The bow / warping degree of the halogen-free and antimony-free flame-retardant laminate may be ≤1.0%, such as 0.1%, 0.3% or 0.2%; The glass transition temperature Tg of the halogen-free and antimony-free flame-retardant laminate may be ≥155°C, and for example 160°C, 155°C or 165°C; The thermal decomposition temperature of the halogen-free and antimony-free flame-retardant laminate may be ≥325°C, such as 360°C, 355°C or 365°C; The antimony content of the halogen-free and antimony-free flame-retardant laminate may be 0 ppm; The chlorine content of the halogen-free and antimony-free flame-retardant laminate may be <900 PPM, such as 250 ppm, 240 ppm or 280 ppm; The bromine content of the halogen-free and antimony-free flame-retardant laminate may be <900 PPM, such as 20 ppm, 18 ppm or 30 ppm; The total content of bromine and chlorine in the halogen-free and antimony-free flame-retardant laminate may be less than 1500 PPM, such as 270 ppm, 258 ppm or 310 ppm.
10. A method for preparing the halogen-free and antimony-free flame-retardant laminate according to claim 9, characterized in that: It includes the following steps: Lamination: Laminating a plurality of halogen-free and antimony-free flame-retardant laminates as claimed in claim 9 with prepregs, and covering the upper and lower surfaces with metal foil or release film to obtain a semi-finished plate; ② The semi-finished plate is subjected to hot pressing and vacuum pressing to obtain; The vacuum value of the hot-pressing vacuum pressing may be 740-800 mmHg, for example 760 mmHg; In step ②, the pressing method may be hot-pressing vacuum segmented pressing, and the hot-pressing vacuum pressing is carried out in stages, including stage one, stage two, and stage three; The first stage may be: the vacuum value is 740-760 mmHg, the temperature at the start of hot pressing is 110-130°C, and the pressure at the start of hot pressing is 5-10 kg / cm 2 The temperature at the end of hot pressing is 200-220℃, and the pressure at the end of hot pressing is 25-30 kg / cm 2 , the hot pressing time is 50-60min; The second stage can be: the vacuum value is 740-760 mmHg, the temperature of hot pressing is 200-220°C, and the pressure of hot pressing is divided into initial pressure, intermediate pressure and late pressure; the initial pressure is 25-30 kg / cm 2 The initial pressure pressing time is 10-15 min; the intermediate pressure is 35-40 kg / cm 2 The mid-term pressure pressing time is 35-40min; the late pressure is 20-25kg / cm 2 The time of the late pressure pressing is 10-15 min; The third stage can be: vacuum or non-vacuum conditions, the temperature at the start of hot pressing is 200-220°C, and the pressure at the start of hot pressing is 20-25 kg / cm 2 The temperature at the end of hot pressing is 110-130℃, and the pressure at the end of hot pressing is 30-35kg / cm 2 The hot pressing time is 20-40min.